Fixing Solutions1: Fascist Temporalities as Remediesfor Liquid Modernity. Issue 1 (February 2015) - Griffin, Roger
Fixing Solutions: Fascist Temporalities as Remedies for Liquid Modernity: This article explores the peculiar temporalities of fascism that emanate from the myth of the eternity of the nation and race that is perpetuated through superhuman, self-sacrificial efforts on their behalf within historical time. It focuses on the role played by modernity as an agent of the «liquefaction» of reality into a perpetual open-ended flux (experienced as decadence and decline), and the attempt by Fascism and Nazism to fix the contours of historical time and restore its shape and purpose through the power of totalitarian organization, political religion, and the manipulation of palingenetic myth. Members of the fascists' organic «national community » were thus exhorted both overtly and subliminally to find a personal transcendent meaning and sense of heroic mission through their active participation in the process of national rebirth. The fascist rebellion against the disenchanted temporality of modernity is located within modernist attempts, not only in every sphere of cultural production, but also in experimental forms of socio-political activism and organization, to create a barrier against the rising flood of disenchantment, relativism, and nihilism arising from modernity.